Teaching Writing with a Web Based Collaborative Learning - Togatorop, Erikson (International Journal of Economics and Financial Issues, 2015)
Writing is known as one of the most important but difficult academic skills. It usually takes so much time for students to master competently and hence tends to be a boring lesson. At the Batam state Polytechnic, there are still many students reluctant to practice English writing and hence their writing ability is still very low. This research tried to teach writing with a web-based collaborative method to increase the students’ interest in writing activities and hence improve their writing performance. Applying a quasi-experiment method, the study implemented a purposive sample; those were two classes that took the Academic Writing Courses. One of the classes which consists of 24 students was treated as the experiment group and the other one which consists of 23 students as the control group. In the experiment class, a web forum was provided and students were asked to share their writings and to give comments or feedback (do peer editing) to their friends’ uploaded writing tasks. The web system provided accumulated mark for the quantity and the quality of those writings and comments or feedbacks. Lecturers also provided feedback before students did revising and rewriting. The control class, on the other hand, was taught with a conventional method. Both groups were compared in the development of their English writing quality by providing pretest and posttest analyzed quantitatively using SPSS. It was found that the average performance of the experiment class better than the control class. Keywords: Writing, Collaborative Learning; Web Based Collaborative Leaning JEL Classifications: M00